Evaluating the impact of women's work on child education: This research was taken from the student's master's thesis. - نصراه, واحدە حمه ویس; رشید, كانیاو ابراهیم كریم (Sulaimani Journal for Humanities, 2020)
There is a historical background for the study field parenting and the role of the women in this regard. It is the reason for the emphasizing on parenting by many different scholars as a phenomenon spread over the world and as a result of the technological advanced the women’s role have also changed to be an essential part of the labour force. The women’s new role as the labour force has its own cost when it comes to parenting. This research is part of my master thesis ‘Women’s working outside their house and its impact on the parenting’ which sociological research with aiming to discover the impact of the women’s job outside their house on their parenting. Research's methodology is a social survey, and to collect information, the researcher has made a questionnaire and has spread in Sulaimani city, specifically inside the education and the health institutions. The research concludes that the women who contributed to this research, did not ignore their responsibility regarding their child’s health and the women’s work outside their home to a large extent have a positive/negative impact on the child’s psychology. Finally, the researcher has shown some.